Ignition and combustion characteristics of single droplets of a crude glycerol in comparison with pure glycerol, petroleum diesel, biodiesel and ethanol. (15th October 2016) - Setyawan, Hendrix Y.; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
Abstract: The ignition and combustion characteristics of single droplets of a crude glycerol were experimentally studied and compared with those of pure glycerol, a petroleum diesel, a biodiesel, and ethanol. A single fuel droplet was suspended at the tip of a silicon carbide fibre undergoing heating, ignition and combustion in an electrically heated horizontal tube furnace at an air temperature ranging from 948 K to 1048 K. The ignition and combustion behaviour of the droplet were recorded using a CCD camera. Ignition delay time, total combustion time, burning rate, and flame standoff ratio were estimated. At a same temperature, the ignition delay time and total combustion time followed the order of pure glycerol > crude glycerol > ethanol > biodiesel > diesel, while the burning rate followed the order of crude glycerol > diesel > biodiesel > ethanol > pure glycerol, suggesting that the impurities, mainly water and methanol, had a profound influence on the combustion characteristics of crude glycerol. The flame standoff ratio slightly decreased after ignition but continuously increased with time afterwards for the crude glycerol and remained almost unchanged for the pure glycerol, indicating the significant influence of impurities on the quasi-steadiness of the flame. Highlights: Glycerol droplet ignition and combustion studied and compared with different fuels. Crude glycerol had longer ignition delay time than diesel, biodiesel and ethanol. Crude glycerol showed the highest burning rate among the fuels studied. Flame standoff ratio of crude glycerol increased with time shortly after ignition. Water and methanol had profound effect on the combustion of crude glycerol.